Libro De Actas CIT2016. XII Congreso De Ingeniería Del Transporte 2016
DOI: 10.4995/cit2016.2016.4207
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of satisfaction factors at urban transport interchanges: Measuring travelers’ attitudes to information, security and waiting

Abstract: Transport interchanges can be considered as a node, where people transfer from one mode to another, and as a place to stay, using facilities and services as well as waiting areas. Reducing disruption of transfer in multimodal trips is a key element for assuring seamless mobility in big cities. Based on previous research (Hernández & Monzón, 2016) this paper aims to explore the predictive capacity of attitudes towards several service factors on general satisfaction with transport interchange. Complement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Mokhlis (2007) and Handriyati, Sunaryo, and Helia (2015) reported dissatisfaction with security and safety services in small terminals. In contrast, Lois, Monzón, and Hernández (2016); Ishak & Madsah (2016); Ikhlaq, et al (2017);and Cheng, Cao, Huang, and Wang (2018) observed user satisfaction with safety and security in large terminals. This difference indicates that the smaller the terminal is, the lower users' satisfaction with safety and security.…”
Section: Figure 2 Level Of User Satisfaction With Terminalsmentioning
confidence: 96%
See 2 more Smart Citations
“…Mokhlis (2007) and Handriyati, Sunaryo, and Helia (2015) reported dissatisfaction with security and safety services in small terminals. In contrast, Lois, Monzón, and Hernández (2016); Ishak & Madsah (2016); Ikhlaq, et al (2017);and Cheng, Cao, Huang, and Wang (2018) observed user satisfaction with safety and security in large terminals. This difference indicates that the smaller the terminal is, the lower users' satisfaction with safety and security.…”
Section: Figure 2 Level Of User Satisfaction With Terminalsmentioning
confidence: 96%
“…The private terminal provided better service than the state terminal. Lois et al (2016) and Cheng et al (2018) reported user perceptions of and satisfaction with services delivered in large and integrated terminals.…”
Section: Figure 2 Level Of User Satisfaction With Terminalsmentioning
confidence: 99%
See 1 more Smart Citation